Rocketeers and gentlemen engineers a history of the American Institute of Aeronautics and Astronautics-and what came before - Crouch, Tom D. (American Institute of Aeronautics and Astronautics, 2006)
Offers an historical account of the American Institute of Aeronautics and Astronautics - and its predecessor organizations, the American Rocket Society and The Institute of the Aeronautical Sciences - and the significant contributions each has made to the evolution of flight.